Instagram Optimization as Digital Marketing Media: Study at a Private Hospital in Batu City - Sunaryo, Nico Christian; Indriani, Wiwin; Fitriasari, Nikma (Fakultas Kedokteran Universitas Brawijaya, 2022)
During the COVID-19 pandemic, up-to-date information becomes a necessity for the public, and social media, especially Instagram, play a significant role in digital marketing, including hospitals. The Instagram account of a private hospital in Batu City had a decreasing performance and has become inactive since the Covid-19 pandemic outbreak. This study aimed to find a solution to the decreasing performance of the hospital's Instagram account to increase visits, trust, and patient satisfaction. This research was a quasi-experimental study with a pre- and post-test design without control conducted from September to October 2021. The intervention carried out was conducting training on optimizing the Instagram features. The research sample was ten people obtained through the total sampling method. The data were analyzed using a descriptive analysis test. The training was carried out twice in a period of one week. The first training session discussed the basic features of Instagram and their use, and discussions on the technical aspects of content creation were done in the second session. Measurement of training understanding was carried out by pre-test and post-test. All points in the questionnaire showed positive points of increasing knowledge after the training. Instagram optimization training at the hospital in Batu City can improve staff understanding of digital marketing and is expected to expand the business and introduce the hospital to new patients.